Dual‐Metal Sites Boosting Polarization of Nitrogen Molecules for Efficient Nitrogen Photofixation. Issue 13 (7th May 2021) - Zhang, Yida; Hou, Tingting; Xu, Quan; Wang, Qingyu; Bai, Yu; Yang, Shaokang; Rao, Dewei; Wu, Lihui; Pan, Haibin; Chen, Jiafu; Wang, Gongming; Zhu, Junfa; et al.
Abstract: Constructing nitrogen (N2 ) adsorption and activation sites on semiconductors is the key to achieving efficient N2 photofixation. Herein, Mn–W dual‐metal sites on WO3 are designed toward efficient N2 photoreduction via controlled Mn doping. Impressively, the optimal 2.3% Mn‐doped WO3 (Mn‐WO3 ) exhibits a remarkable ammonia (NH3 ) production rate of 425 µmol gcat. −1 h −1, representing the best catalytic performance among the ever‐reported tungsten oxide‐based photocatalysts for N2 fixation. Quasi in situ synchrotron radiation X‐ray spectroscopy directly identifies that the Mn–W dual‐metal sites can enhance the polarization of the adsorbed N2, which is beneficial to the N2 activation. Further theoretical calculations reveal that the increased polarization is originated from the electron back‐donation into the antibonding orbitals of the adsorbed N2, hence lowering the reaction energy barrier toward the N2 photofixation. The concept of dual sites construction for inert molecule activation offers a powerful platform toward rational design of highly efficient catalysts for nitrogen fixation and beyond. Abstract : The optimal 2.3% Mn‐doped WO3 exhibits an impressive NH3 production rate of 425 µmol gcat. −1 h −1 . Further quasi in situ synchrotron radiation X‐ray spectroscopy and theoretical calculations reveal that the Mn–W dual‐metal sites can enhance the polarization of the adsorbed N2, hence lowering the reaction energy barrier toward the N2 photofixation.